From Peers to Progress: Implementing a Peer Tutor Based Cooperative Model for better Learning Results - Chuduriah Sahabuddin; Muhammad Ali P; Miftahul Jannah; Iramaya (Universitas Sulawesi Barat, 2025)
This study aims to improve student learning outcomes through the implementation of peer tutoring-based cooperative learning. The research employs classroom action research with a total of 27 students involved in two cycles of learning. The cooperative model applied uses the STAD (Student Teams Achievement Division) type. Each cycle consists of three meetings and one final test at the end of the cycle. The results indicate that in the first cycle, the percentage of students achieving mastery in learning outcomes was 59.26%, which significantly increased to 100% in the second cycle. The research process involves stages of planning, action, observation, and reflection to ensure smoothness and effectiveness in implementing the teaching method. Overall, this study concludes that peer tutoring-based cooperative learning can be effectively applied to enhance student performance and suggests continuing similar research in different contexts regarding materials and educational levels to broaden the generalization of results.